Breve historia de la Facultad de Ciencias Jurídicas y Políticas de la Universidad Nacional del Altiplano de Puno, camino al bicentenario de su creación - Espinoza Coila, Michael (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2020)
The purpose of the article is to concisely expose the historical development of the Faculty of Legal and Political Sciences of the National University of the Altiplano of Puno in its 164 years of creation (1856) and 38 years of reopening (1982), a plot that is projected in three centuries since the University of San Carlos de Puno was erected to the present, which is inserted in a context of search for quality, licensing and university accreditation, added to that, the Covid-19 pandemic. In that order, it tries to provoke a reflection through its academic, administrative and social projection bodies of a Faculty that has had a splendid trajectory in its formative work, and that now holds the accreditation that ensures levels of educational quality that are destined to remain for the forging of legal professionals with a broad and compromising perspective of justice.